Sosialiasi Pemilahan Sampah di Desa Kedungrandu: Solusi Pengeloaan dan Pemanfaatan Sampah Rumah Tangga - Syahid Nur Khomsyi; Mega Yuliani Ramme; Gabriella F Pandiangan; Brian Nugraha Wiyono; Aina Latifa Riyana Putri (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2024)
Waste is residual material in solid, liquid, or gas form that is present in people's lives. All human activities inevitably produce waste, including in Kedungrandu Village. Waste management using the Collect-Transport-Dispose principle is irrelevant because it does not solve the source of the household waste problem. As the highest waste producer, household waste management is critical to reduce the volume of waste disposed of in landfills. The most appropriate management and handling of household waste are done by sorting waste based on its characteristics. This activity will shape the role and encourage the community to participate in handling their household waste so that it is hoped that the amount will be reduced. The method used is a descriptive survey with a study design for filling out a questionnaire, observation/field survey method. The survey results show that the waste management system in Kedungrandu Village is not good because there is no rubbish dump and there is a lack of knowledge and skills in waste management. Based on the average survey results, show that 100% of people do not understand the difference between organic and inorganic waste and 60% of people have difficulty managing household waste. The benefits of this socialization are that people can sort waste according to their characteristics, have awareness and concern for the environment, and find the right solution to overcome waste. management problems. Potential problems in community-based waste management education and planning of subsequent activities are important for the sustainability of waste management.